Essays on the relation between higher education and the labour market - Hou, S (2023)
An important theme in the economic analysis of education is the relation between students’ decisions to invest in education and the implication of these investments for their wages and productivity on the labour market. Despite being an area of very active research, there is much that remains unknown about why and how students make education decisions, whether these decisions are optimal, and what the effect of these investments are. This thesis contributes to the literature by exploring three questions directly or indirectly relating to these open issues. In the first essay, “Individual and Aggregate Mismatch in Higher Education”, I study the broad public concern that there are too many students who choose to go to university. I produce a model that combines endogenous education choice with heterogeneity and uncertainty in returns, with a labour market framework based on matching that creates supply and demand-like wage responses. In this setting, uncertainty about returns generates individual education mismatch, while endogenous education choice in a matching market generates aggregate inefficiency in education choice. In the second essay, “The Butcher, the Brewer, or the Baker: The Role of Occupations in Explaining Wage Inequality”, we study the importance of the occupational structure in wage determination. We introduce a model that nests Abowd et al. (1999), and estimate it on British data. We find that even if workers and firms were identical, 25% of current log-wage variance would remain, due solely to heterogeneity between occupations. Thus, occupational pay-premia are important sources of wage heterogeneity in the economy. In the third essay, “Determinants of University Subject Choice in the UK”, I study the elasticity of students’ demand for university courses in particular subjects with respect to their expected earnings in that subject. I find that earnings, defined as earnings at age 25 or as lifetime earnings, are positively associated with choice probability, although the quantitative impact of expected earnings on subject choice is not large. I document substantial differences in choice probability between students of different sexes, ethnicities and to a lesser extent, socio-economic classes.